SLOPE STABILITY EVALUATION OF VOLCANIC SOIL AT LIWA-BUKIT KEMUNING WEST TRAFFIC ROAD, WEST LAMPUNG - Prahara Iqbal; Asep Mulyono; Arifan Jaya Syahbana (Badan Geologi, 2017)
Slope stability modeling conducted on two cut slopes which has two different volcanic soil types at Liwa-Bukit Kemuning west traffic road, Lampung Barat. Numerical simulations is the method which used. This method describe changes in the value of the safety factor when it rains. Results of the analysis illustrates that the highest safety factor was obtained on the slopes of sandy soil. Modeling illustrates also the decreasing safety factor when it rains.